Emulgel: an effective drug delivery system. (3rd August 2021) - Talat, Maria; Zaman, Muhammad; Khan, Rahima; Jamshaid, Muhammad; Akhtar, Muneeba; Mirza, Agha Zeeeshan
Abstract: Background: Emulgels are the emerging drug delivery system nowadays that has become popular for the delivery of hydrophobic drugs. This formulation is considered a novel type of drug delivery system and a mixture of emulsion and gel. Objective: The objective of this review is to throw light on the preparation of emulgels and their evaluation which will conclude how important these dosage forms are. In the coming years, it will be most commonly used because it is easy to use and enhances patient compliance. Conclusion: Emulgels are easily removable, spreadable, thixotropic, greaseless, have a pleasing appearance, emollient, long shelf life, and transparent. In the present era, the emulgels are being used for the delivery of many drugs like analgesics, anti-inflammatory, anti-acne and anti-fungal. Hence, it is of great pharmacological importance and is relatively free of side effects.